Potential of Pirdot Leaf (Saurauia vulcani Korth.) as Immunomodulator: JAK-STAT Pathway and Turandot A Gene Expression in Drosophila melanogaster Hyperglycemia Model - Manik, Enisantaria Br (International Journal of Ecophysiology, 2025)
Type 2 diabetes mellitus (T2DM) is a global health issue characterized by chronic hyperglycemia, insulin resistance, immune system dysregulation, and increased mortality rates. Therapeutic approaches based on natural immunomodulators represent a potential strategy for managing this disease. Saurauia vulcani Korth. (pirdot), an endemic plant of Indonesia, is known to contain bioactive compounds such as flavonoids, saponins, and triterpenoids, which exhibit antioxidant, antidiabetic, and immunomodulatory activities. Drosophila melanogaster, which has a high level of genetic homology with humans, is used as a model for insulin resistance through the induction of a high-sugar diet. One of the key genes in the immune response of this organism is Turandot A (TotA), which is expressed in response to stress and regulated by the JAK-STAT signaling pathway.